(untitled) (Jurnal Rekayasa Mesin dan Inovasi Teknologi, 2023)
Fuel consumption is the consumption of fuel in the engine, usually using units of liters/hour or gallons/hour. fuel consumption is one indicator of the efficiency of engine performance. The type of fuel and engine capacity have an effect on fuel consumption. Load factor is the calculation of the useful value of the available load capacity of the mode of transportation/unit. Engine life time to overhaul (ELTO) is an engine overhaul prediction in what hour meter, based on fuel consumption. In this research, it is sought how the influence of fuel consumption on the load factor and life time to overhaul the Cummins QSK 60 MCRS engine. This research was conducted at a workshop in Sangatta, East Kutai Regency, East Kalimantan, precisely in the coal mining area of PT. Sangatta Mine Site. In this study, researchers used qualitative research. To explain this research, the researcher used a qualitative descriptive approach to find the value of the load factor percentage and determine the estimated engine life to overhaul (ELTO). The highest level of load factor percentage is 73.3% with a fuel consumption of 265 gals/hr. For the lowest percentage of the loadfactor is 71.6% with a fuel consumption of 259 gals/hr. The highest value for engine life to overhaul (ELTO) is 12,785 hours with a fuel consumption of 259 gals/hr. And the lowest value for engine life to overhaul (ELTO) is 12,488 hours with a fuel consumption of 265 gals/hr.